Pengaruh Bauran Pemasaran Terhadap Kepuasan Wisatawan Domestik di Daya Tarik Wisata Kawasan Luar Pura Uluwatu - Bujung, Glend Elisa Alexander; Liestiandre, Hanugerah Kristiono; Aridayanti, Dewa Ayu Nyoman (Journal of Applied Science in Tourism Destination, 2023)
Purpose : Marketing mix is ??a strategy that is often implemented in a company or tourist attraction. This strategy is related to determining how the company or tourist attraction including Outer Area of Uluwatu Temple Tourist Attraction offers product accompanied by several other supports in the form price, place, promotion, people, process and physical edivence strategies for certain market segments. The purpose of this study was to determine how the effect of 7p's marketing mix on the satisfaction of domestic tourists simultaneously and partially. Methodology: The samples in this research is 271 domestic tourists. Questionnaires were distributed online and offline by accidental sampling and analyzed using multiple linear regression. Findings : The results of the simultaneous analysis show that the 7p marketing mix has a positive and significant effect and partially the product, price and place variables have a positive effect. While, the promotion, people, process and physical appearance variables have no positive and significant effect. Based on the coefficient of determination  in this result is the percentage the effect of the 7p marketing mix (product, price, place, promotion, people, process, physical appearance) on the satisfaction of domestic tourists is 20.3%, while the remaining 79.7% is explained or effected by other variables not examined in this research.